On the Margins of the Manthropocene: Semiotic Violence against Women in Politics as a form of Diamesic Creativity - Balirano, Giuseppe (Margins/Marges/Margini, 2024)
This paper aims to shed light on the impact of 'semiotic violence' on women in politics, emphasizing the importance of using language as a catalyst for positive social change in order to fight gender-based violence in all its manifestations. The study specifically investigates the role of the Manthropocene in perpetuating 'semiotic violence’ against women in politics, with a specific focus on the recent international media use of sexist language when addressing Finland’s first female Prime Minister, Sanna Mirella Marin. The analysis examines how gendered insults, slurs, and derogatory communication techniques are employed to undermine the political authority of the politician, thereby perpetuating discrimination and violence. Given this context, I argue that collective societal action is necessary to challenge and reject sexist attitudes and behaviours, including those facilitated through 'diamesic creativity'.